On the scattering of electromagnetic waves by bi-isotropic spherical shell - Gennady Shushkevich; Svetlana Shushkevich; Aleksandr Kuts (Advances in Mechanical and Materials Engineering, 2017)
In this article an analytical solution of the problem of scattering of electromagnetic waves on bi-isotropic spherical shell has been presented. Secondary electromagnetic fields are introduced as a superposition of spherical vector wave functions. The solution of the boundary problem is reduced to solving a system of linear algebraic equations for the coefficients which are included in the presentation of the secondary fields. The formula to calculate the directional diagram of electric field in the far field and numerical results for different values of parameters have been obtained. The results may find practical application in the development and design of electromagnetic screens.